Pb Toxicity on Gut Physiology and Microbiota - Liu, Wenya; Feng, Hai; Zheng, Shuilin; Xu, Shuaishuai; Massey, Isaac Yaw; Zhang, Chengcheng; Wang, Xiaoyan; Yang, Fei (Frontiers in Physiology, 2021)
Abstract Lead (Pb) is a toxic heavy metal, having profound threats to the global population. Multiple organs such as kidney, and liver, as well as nervous, hematologic, and reproductive systems, are commonly considered as the targets of Pb toxicity. Increasing researches reported that the effects of Pb on gastrointestinal tracts are equally intensive, especially on intestinal microbiota. This review summarized Pb toxicity on gut physiology and microbiota in different animal models and in humans, of which the alterations may further have effects on other organs in host. To be more specific, Pb can impair gut barrier and increase gut permeability, which make inflammatory cytokines, immunologic factors, as well as microbial metabolites such as bile acids (BA) and short-chain fatty acids (SCFAs) enter the enterohepatic circulation easily, and finally induce multiple systematic lesion. In addition, we emphasized that probiotic treatment may be one of the feasible and effective strategies for preventing Pb toxicity.